Prevalence and perception of cigarette smoking among out of school adolescents in Birnin Kebbi, North-western Nigeria - Gana, Godwin Jiya (Pan Afr Med J, 2018)
INTRODUCTION: cigarette smoking is on the increase among adolescents' especially in developing countries and is a leading cause of premature morbidity and mortality worldwide. Adolescents incorrectly perceive that cigarette smoking is less risky than other behaviors such as alcohol consumption and drug use. This study assessed the prevalence and perception of out of school adolescents on cigarette smoking in Birnin kebbi metropolis of Kebbi state. METHODS: This is a cross-sectional mixed methods study. For quantitative data, respondents were selected using two-staged sampling technique. Semi structured interviewer-administered questionnaire was used. Univariate and bivariate analysis was done as appropriate using Epi-info software. Focus Group Discussion guide was used for qualitative data collection. Narrative synthesis was used for qualitative data analysis. RESULTS: The proportion of respondents who had ever smoked cigarettes was 32.2% while 20.8% currently smoke. Most of the respondents (84.1%) perceived that cigarette smoking was harmful and that passive smoking was dangerous to their health (70.8%). Smokers had a significantly lower risk perception about smoking compared to non-smokers (p < 0.005). CONCLUSION: The prevalence of cigarette smoking among out of school adolescents is high with smokers having lower risk perception compared to non-smokers. There is an urgent need to create awareness about the specific dangers associated with cigarette smoking, the transient nature of its perceived benefits and the fact that the risks associated with smoking are severe.